# Differentiating an infinite sum

Some other summation formulas can be obtained by differentiating the above equations on both sides.

Assume $|r|<1$. Show that
$$a+2ar+3ar^2+\cdots = \frac{a}{(1-r)^2}$$ by starting with the geometric series formula. This seems to be trivial to prove by differentiation of both sides of the infinited geometric series formula. Is this a legal operation?

#### Solutions Collecting From Web of "Differentiating an infinite sum"

Interchanging the order of differentiation and infinite summation is not valid in general, but it can be validated under certain circumstances.

For example, assume the power series $\sum a_n x^n$ has the radius of convergence $R > 0$. Then on the open interval $(-R, R)$, you can freely interchange the order of differentiation/integration and infinite summation: on $|x| < R$,

• $\displaystyle \frac{d}{dx} \sum_{n=0}^{\infty} a_n x^n = \sum_{n=0}^{\infty} a_n \frac{dx^n}{dx} = \sum_{n=1}^{\infty} n a_n x^{n-1}.$
• $\displaystyle \int_{0}^{x} \sum_{n=0}^{\infty} a_n t^n \, dt = \sum_{n=0}^{\infty} a_n \int_{0}^{x} t^{n} \, dt = \sum_{n=0}^{\infty} \frac{a_n}{n+1} x^{n+1}.$

Note that the radius of convergence of the geometric series

$$a + ax + ax^2 + ax^3 + \cdots$$

is exactly $R = 1$ unless $a = 0$. In particular, your operation is totally legal.

If you’re concerned with infinite terms, what you can do instead is differentiate finite terms, and then take the limit as $n \rightarrow \infty$. So begin with

$\displaystyle\sum_{k=0}^{n}{ar^k} = \dfrac{a(1-r^n)}{1 – r}$

Differentiating this with respect to $r$ gives us,

$\displaystyle\sum_{k=1}^{n} kar^{k-1} = \dfrac{a}{(1-r)^2}\big((1-r)(-nr^{n-1}) + (1 – r^n)\big)$

Taking the limit of both sides, and assuming that $|r|<1$ finishes the proof.